Negotiating Value: A Case Study of the Gothenburg Book Fair - Lenemark, Christian (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
The Gothenburg Book Fair is one of the most important cultural events in Scandinavia today. Since 1985, it has grown into a meeting place for book lovers, librarians, and people in the book industry. However, it has also been surrounded by scandals and controversies. Inspired by Brian Moeran’s notion of the book fair as “a tournament of values,” and Barbara Herrnstein Smith’s constructivist approach to value, this article analyzes the Gothenburg Book Fair as an arena for negotiating value. The article first discusses how the value of the Gothenburg Book Fair has been under constant negotiation since its inception, and then examines how different actors participated in consolidating the fair’s value and function at the beginning of the 2010s. Finally, it considers the intensive debate about the Gothenburg Book Fair in 2016–2017, due to the decision to allow the extreme-right newspaper Nya Tider to have a stand in the exhibition halls, which above all resulted in a renegotiation of the book fair’s social and economic value. Through this diachronic and historical perspective, the article shows how a more pronounced theoretical value perspective in relation to book fairs and literary festivals provides new knowledge about these types of literary events and their role in literary culture as a whole.